Inadequate health literacy and higher healthcare utilisation among older adults in Switzerland: cross-sectional evidence from a population-based study (Swiss Medical Weekly, 2024)
BACKGROUND AND AIM: Population ageing in Switzerland poses significant challenges, including for the healthcare system. Inadequate health literacy can hinder individuals’ ability to seek appropriate treatments and navigate the healthcare system efficiently. This study explores the associations between health literacy and the number of consultations with general practitioners and healthcare specialists in a population-based sample of adults aged 58+ in Switzerland.METHODS: We used data from 1424 older adults who participated in Wave 8 (2020) of the Survey of Health, Ageing, and Retirement in Europe (SHARE). The analysis focuses on two outcomes: the reported number of consultations with (1) general practitioners or (2) healthcare specialists in the year prior to the interview. Health literacy, i.e. the ability to find, understand, assess and apply health information, is measured using the short version of the European Health Literacy Survey questionnaire (HLS-EU-Q16). The final health literacy score ranged from 0 to 16 and was categorised into three health literacy levels: inadequate (0–8), problematic (9–12) and sufficient (13–16). Bivariate analyses were conducted using Kruskal-Wallis tests. Partial associations were examined using multivariate generalised Poisson regression models controlling for key sociodemographic, regional and health-related variables.RESULTS: Overall, 68.5% of the respondents were classified as having sufficient health literacy, while the health literacy level of 23.5% and 7.9% of respondents was classified as problematic or inadequate, respectively. The median number of general practitioner consultations and specialist visits was 2 and 1, respectively, both with an interquartile range of 1. Lower levels of health literacy were statistically significantly associated (p = 0.0011) with a higher number of general practitioner consultations in the year prior to the interview. By contrast, we did not find any significant association between health literacy and the number of specialist consultations.CONCLUSION: This study finds that lower health literacy is associated with higher healthcare utilisation for older adults in Switzerland. The findings may suggest that general practitioners could have a significant role as advisors for individuals with low levels of health literacy, while a similar pattern is not observed for specialists. This discrepancy might be attributed, at least in part, to the role of general practitioners as intermediaries between patients and specialised care providers. Ensuring accessibility to general practitioners, particularly for individuals with low health literacy, could prove to be a beneficial strategy in addressing the healthcare requirements of this particularly vulnerable patient group. Additionally, improving health literacy in the population may provide further health benefits and lead to resource savings.